Autoimmune Hemolytic Anemia After Cyanocobalamin Replacement in a Patient With a Previous Diagnosis of Pernicious Anemia: A Case Report (2020)
ABSTRACT: Pernicious anemia (PA) is associated with other autoimmune diseases, such as hypothyroidism, type 1 diabetes mellitus (DM1), Addison's disease, and vitiligo. The association between PA and autoimmune hemolytic anemia (AIHA) is rare, with less than 30 cases reported in the literature. In this paper, we report a case of a patient with a confirmed diagnosis of PA, who, six months after starting treatment with cyanocobalamin, presented with severe hemolysis with a positive direct antiglobulin test (DAT) for warm antibodies; the patient responded well to glucocorticoid treatment. AIHA in PA patients can be triggered by cyanocobalamin replacement due to the expression of membrane antigens by mature red blood cells entering into the peripheral circulation. This association should be considered because these patients, in addition to cyanocobalamin replacement, will require immunosuppressive treatment, usually with glucocorticoids.